Precocious weaning: habits of living among mothers attended at a Primary Health Care center in Fortaleza, Ceara - Andrade, Mônica Pinheiro; Oliveira, Maria Ivoneide Veríssimo de; Bezerra Filho, José Gomes; Bezerra, Maria Gorete Andrade; Almeida, Lívia Silva de; Veras, Maria Altamira Castro e (Rev Rene, 2009)
The aim of this research was to characterize the social economical profi le problematic questions and attitudes of mothers who weaned their children precociously and were seen at a primary health care unit in Fortaleza – Ceara from June to August, 2007. It is a descriptive, explorative study, using quantitative approach, whose participants were 50 mothers with children who were less than one year of age. As a result we could observe that 58% were more than 25 years of age; 46% had high school level, 82% had accomplished pre natal medical care; 54% were primipara 66% didn’t work, 64% had low income, 54% had undergone cesarean section, 66% were oriented, 38% by the nurse, 54% breastfed up to 6 months and protect against diseases, 22% offer Just mother’s Milk and nipple formation, 46% think breastfeeding is comfortable, 52% had diffi culties in the practice, 78% had doubts in the technique, 88% the baby grows healthy. We may conclude that although most of these women consider mother’s Milk the Best option to feed the baby, weaned precociously. Thus, we can observe that the received information concerning the appropriate time for exclusive breastfeeding and its importance for the baby don’t seem enough to conduct appropriate practice.